Simulation, technical-economic evaluation and risk analysis of the purification of different bio-oils obtained by the fast pyrolysis process - Stéphani Caroline de Lana Arêdes; Betânia Hoss Lunelli; Fábio de Ávila Rodrigues (The Journal of Engineering and Exact Sciences)
Biomass is a natural compound that originates from various forms of organic matter. One way to transform biomass into value-added products is through the fast pyrolysis process, which is a thermochemical process that produces solid, liquid and gaseous compounds. The main product of this process is the bio-oil, found in the liquid phase and containing a wide range of value-added compounds that can be obtained through extraction and distillation. Simulation is an important tool for predicting, modeling and understanding the feasibility of the desired process, along with economic analysis of risks and uncertainties, which are useful techniques for studying the feasibility of projects. In this context, this work aimed to carry out the simulation using the Aspen Plus ® process simulator, the analysis of economic viability and the analysis of risks and uncertainties of the process of separation and purification of bio-oil compounds, derivatives of wood from eucalyptus, eucalyptus residues and sugarcane bagasse. After completing these steps, the project achieved a good result, with desired products being obtained with a considerable degree of purity for commercialization. Economically, all processes were viable, obtaining a good return on investment and a short payback period, despite the high costs involved. Even considering risks and uncertainties, including the variation in the cost of raw materials and production capacity, the investment still returned good results, demonstrating that the project is economically viable even under these circumstances.